Developing Public-Private Partnerships for effective access and use of climate information services by farmers and pastoralists in the Great Green Wall intervention zone of Mali - Findings from the project “Addressing SDG15 in the Sahel by Building Pathways for Transforming Food and Land Systems in a Climate Crisis” - Traoré, Bouba; Bouaré, Yaya; Nikoi, Gordon; Zougmoré, Robert B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This research activity pursues three specific objectives: 1)Evaluate existing collaboration and mechanisms for mainstreaming CIS and agro-advisories into the activities conducted by the Great Green Wall National Agency of Mali; 2) Develop Public-Private Partnerships for the sustainable management of climate risks in the zone of the Great Green Wall; 3) Define activities, roles and responsibilities and possible contractual issues for the sharing of costs and benefits between the actors involved in Climate Information Service activities in Mali.